2013
DOI: 10.2113/gssgfbull.184.4-5.441
|View full text |Cite
|
Sign up to set email alerts
|

Transient active deformation in Tainan tableland using persistent scatterers SAR interferometry

Abstract: Persistent scatterers SAR interferometry (PS-InSAR) was employed to monitor surface deformation in and around the Tainan tableland using 20 advanced synthetic aperture radar (ASAR) images from the ENVISAT satellite taken during the period from 2005 May 19 to 2008 September 25. In our study, we have found that the uplift rate of the northern Tainan tableland is faster than the southern tableland. The slant range displacement (SRD) rate for the area north along the precise leveling array is about 5 to 10 mm/yr w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…The active present‐day growth of the Tainan anticline is probably the best‐monitored fold growth on Earth. Leveling, GPS, and InSAR measurements covering different time periods since 1996 (Ching, Hsieh, et al, ; Huang et al, , Huang, Bürgmann, et al, ; Wu et al, ; CGS, ) converge to an average present‐day uplift rate of 9–12 mm/a of the tableland relative to the Coastal Plain. Horizontal velocities based on continuous and campaign GPS measurements between 2002 and 2014 (CGS, ) progressively decrease from the toe of the foothills, in the east, to the coastline, in the west (Figure ), clearly imaging the consumption of westward shortening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The active present‐day growth of the Tainan anticline is probably the best‐monitored fold growth on Earth. Leveling, GPS, and InSAR measurements covering different time periods since 1996 (Ching, Hsieh, et al, ; Huang et al, , Huang, Bürgmann, et al, ; Wu et al, ; CGS, ) converge to an average present‐day uplift rate of 9–12 mm/a of the tableland relative to the Coastal Plain. Horizontal velocities based on continuous and campaign GPS measurements between 2002 and 2014 (CGS, ) progressively decrease from the toe of the foothills, in the east, to the coastline, in the west (Figure ), clearly imaging the consumption of westward shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous geodetic studies proposed the occurrence of aseismic slip on the Houchiali fault and Tainan detachment, as steady creep during periods of a few years or as transient events associated with or following local and regional earthquakes (Butcher and Huang, ; Ching, Rau, et al, ; Fruneau et al, ; Huang et al, , , Huang, Bürgmann, et al, , Huang, Hsin, et al, ; Wu et al, ). Transient events, in particular, were observed not only on the tableland and across the Houchiali fault but also across some of the hinterland back thrusts (Figure c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on SAR interferometry (Fruneau et al 2001;Huang et al 2006Huang et al , 2009 suggested that the uplift of Tainan tableland is associated of active folding controlled by west-vergent blind Tainan fault and east-vergent Hochiali fault. In addition, a variation of LOS rate across the Hochiali fault was revealed by PS-InSAR (Wu et al 2013) deformation. It implies that the seasonality and hydro-geological condition also play a crucial role for the transient deformation (Huang et al 2016a).…”
Section: Tectonic Setting Background Seismicity and Active Structurmentioning
confidence: 98%
“…Over the years, precise leveling, global positioning system (GPS) and interferometric synthetic aperture radar (InSAR) have proven to be powerful techniques in the field of geodesy. Many studies have applied these techniques for land subsidence monitoring and prediction (Reilinger et al 1977;Dixon 199l;Yu and Chen 1994;Galloway et al 1998;Massonnet and Feigl 1998;Ferretti et al 2001;Sato et al 2003;Chang et al 2004;Hooper et al 2004Hooper et al , 2007; Galloway and Burbey 2011; Yen et al 2011;Wu et al 2013). …”
Section: Introductionmentioning
confidence: 99%